ROLE OF COMMUNICATION TOOLS IN THE PROMOTION OF MUSIC: संगीत के प्रचार प्रसार में संचार साधनों की भूममका - Nagar, vidhi (International Journal of Research -GRANTHAALAYAH, 2015)
In the modern era, it would be like glorifying the media to include every media related to human life from fingernail to fire. It is the medium that has the ancient ideology and values ​​of society as popular with globalization and modern thought stream The society, which is inhabited by the rajas, has also been plunged to the present day, seeing the reach and impact of media in particular, a frazzled Schmimiya state has been born, especially in order to achieve the concept of global global culture of Mishwa. It is from these media that we can see the news of events at the far end of the world, as far as music is concerned, it is possible that we can cope with many ages, ages and lives. When it is achieved in its present form, in the same continuous stream of time, it is infectious, sometimes Pallimat and Sushobhamat are the modern communication mediums in this stream are also pushing it deeper. Achayat Sharangadei has said in his famous book, Song Ratnakaresh आधुमनक काल में मानि जीिन से संबंमधत हर क्षेत्र को नख से मशख तक प्रभामित करने िाले संचार माध्यमों को ममहमादृमंमित करनाए सूरज को मदया मदखाने जैसा होगा द्य यह िह माध्यम है मजसने िैश्वीकरण ि आधुमनक मिचार धारा से लबरेज समाज के सार्थ ही पुरातन मिचारधाराए मान्यताओं ि रीमत ररिाजों से सराबोर समाज को भी तह तक प्रभामित मकया है द्य िततमान समय में संचार माध्यमों कीए मिशेषकर मीमिया की पह ंच और प्रभाि को देखते ह ए ही एक फ्रेज़ श्मीमिया स्टेटश् का जन्म ह आ है द्य मिशेषकर मिश्व के श्ग्लोबल मिलेजश् की पररकल्पना को प्राप्त करने में सबसे महत्िपूणत हार्थए इन्हीं संचार माध्यमों का हैए इन्हीं की बदौलत हम कोसों दूर की क्याए मिश्व के दूरस्र्थ छोर की खबरोंए घटनाओं का उसी पल अिलोकन कर सकते है द्य जहां तक संगीत का सम्बन्ध हैए यह सित मिमदत है मक अनेकों युगोंए कालोंए ि पररमस्तमर्थयों का सामना करते ह ए यह अपने िततमान स्िरुप को प्राप्त ह आ है द्य समय की इसी सतत प्रिामहत धारा में कभी यह संक्रममत ह आए तो कभी पल्लमित ि सुशोमभत द्य इसी धारा क्रम में आधुमनक संचार माध्यम भी इसे गहरे तक प्रभामित कर रहे है द्य आचायत शारंगदेि ने अपने प्रमसद्ध ग्रन्र्थ श्संगीत रत्नाकरश् में कहा है